Construction and analysis of finite element model of defected articular cartilage - Lin, Yuan (Saudi J Biol Sci, 2020)
In order to construct a finite element model of defected articular cartilage, the mechanical behavior and degeneration of articular cartilage after injury were studied. The simplified analytical models of normal and defected articular cartilage and finite element models were established, respectively. Firstly, the analytical solution model and finite element model of hollow defect were constructed by using the elasticity theory of multi-hollow medium. Then, the analytical results of each model were calculated and programmed. The software MATLAB was used for programming calculation. Finally, a finite element solid model of defected articular cartilage was established by using human femoral joint. The solid model was analyzed and calculated by magnetic resonance imaging (MRI). The results showed that when the radius of articular cartilage defect r = 0, i.e. there was no defect in articular cartilage, the internal pore pressure of the defect cartilage was the largest, and its pore pressure value was [Formula: see text] pa. When the depth of articular cartilage defect r = 0, i.e. there was no defect in articular cartilage, the internal pore pressure of the defect cartilage was the largest, and its pore pressure value was [Formula: see text] pa, and it gradually decreased towards the outer boundary of cartilage. When the surface of femoral cartilage began to defect, with the increase of the depth of the defect (from shallow to deep), the maximum pore pressure in the defect cartilage gradually decreased, but the speed is slowly. With the increase of the defect radius, that is, the area of the defect, the maximum pore pressure in the defect cartilage gradually decreased. When there was no defect of articular cartilage, the internal pore pressure of the defect cartilage was the maximum, the value of pore pressure was [Formula: see text] pa, the value of pore pressure at the contact position of femoral cartilage was the largest, and it gradually decreased towards the outer boundary of cartilage. At the same location, the pore pressure of normal cartilage was significantly higher than that of defected cartilage. With the change of defect location, the pore pressure was reduced accordingly. Moreover, when the defect position moved from the outside to the inside, the corresponding pore pressure value was decreased gradually. To sum up, the finite element model of defected articular cartilage based on porous elasticity theory has better calculation ability, which proves the validity of the finite element software, and provides a strong basis for future model establishment and clinical treatment of articular cartilage.